EFFECT OF MADHU TAILIKA BASTI AND SHAMANA AUSHADHI IN POLY-CYCSTIC OVARIAN DISEASES - M. Reddi, Shridevi.; V, Anupama.; Mishra, Baidyanath (International Journal of Ayurveda and Pharma Research, 2015)
Polycystic ovarian disease (PCOD) is emerging as a main cause of menstrual irregularities, mainly observed in age group of 12-45 yrs of age. Based on present data available, 5-15% of females suffer from this condition that includes symptoms like obesity, irregular menstrual cycle, hirsutism etc. In Ayurveda though exact correlation cannot be ascertained, it can be better explained under Rasa nimittaja vyadhi, where the involvement of Medo dhatu, Vata and Kapha doshas are seen. Madhutailika basti which carries numerous positive clinical results as per the classical reference based on the various pharmacological properties on Medo dhatu dustigata vyadhis, because of its ingredients. Based on the available references, Madhutailika basti along with other Shaman ausudhis are taken for a pilot observational study at Shri Kalabyraveshwaraswamy Ayurvedic Medical College Hospital & Research Centre Vijayanagar Bangalore. Post approval of the institution ethical committee, Madhutailika basti was administered to selected patients for a period of 8 days followed by administration of Shaman aushadis for a period of next 3 months. The overall results showed marked improvement in 70%, moderate improvement in 20% of the patients. All patients completed the study successfully without any drop outs.